Determinants of Islamic Banks' Financial Performance in ASEAN Countries - Arya Ramadhani; Aufar Fadlul Hady; Fira Nurafini (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to examine the determinants of Islamic banks’ financial performance in selected ASEAN countries, namely Indonesia, Malaysia, Thailand, and Brunei Darussalam. The financial performance of Islamic banks is assessed using ROA, with important explanatory variables including the CAR, NPF, and FDR. This study takes a quantitative approach, using secondary data from Islamic banks' annual financial reports for the period 2020 – 2024. The data are evaluated using panel data regression, and model selection is conducted using the Chow test, Hausman test, and Lagrange multiplier test, which indicate that the Random Effects Model (REM) is the most appropriate estimation approach. The results show that CAR has a positive and significant effect on the financial performance of Islamic banks, whereas NPF and FDR have negative and positive coefficients, respectively, but do not show a significant effect on ROA. These results indicate that capital adequacy mainly drives the financial performance of Islamic banks in ASEAN, whereas credit risk and liquidity levels have little effect on profitability. This could be because of the risk-sharing nature inherent in Islamic banking practices.